2016
DOI: 10.1002/cam4.664
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐responsive miR‐124 and miR‐144 reduce hypoxia‐induced autophagy and enhance radiosensitivity of prostate cancer cells via suppressing PIM1

Abstract: Cancer cells in hypoxia usually make adaptive changes in cellular metabolism, such as altered autophagy. This might be a cause of enhanced radioresistance in some types of cancer. In this study, we investigated hypoxia‐responsive miRNAs in two prostate cancer cell lines (DU145 and PC3). This study firstly reported that hypoxia induces further downregulation of miR‐124 and miR‐144, which might be a result of impaired dicer expression. These two miRNAs can simultaneously target 3′UTR of PIM1. Functional study sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 23 publications
2
36
0
Order By: Relevance
“…reported that knockdown of Pim1 significantly attenuated hypoxia-induced autophagy, whereas Pim1 overexpression markedly enhanced hypoxia-induced autophagy in prostate cancer cells [35]. We found that Pim1 overexpression enhanced autophagy and decreased apoptosis in vitro in NRVMs in the presence of hypoxia and H 2 O 2 .…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 50%
“…reported that knockdown of Pim1 significantly attenuated hypoxia-induced autophagy, whereas Pim1 overexpression markedly enhanced hypoxia-induced autophagy in prostate cancer cells [35]. We found that Pim1 overexpression enhanced autophagy and decreased apoptosis in vitro in NRVMs in the presence of hypoxia and H 2 O 2 .…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 50%
“…In these cancers, some established tumor suppressive genes were found to be the direct targets of miR-144, such as PTEN in nasopharyngeal carcinoma (Song et al, 2019), and ARID1A in clear cell renal cell carcinoma (Xiao et al, 2017). In prostate cancer, miR-144 was shown to enhance radiotherapy sensitivity and suppress hypoxia-induced autophagy by inhibiting PIM1 expression (Gu et al, 2016). Furthermore, miR-144 could decrease the proliferative ability and induce apoptosis in CRPC cells by targeting CEP55 (You and Zhang, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they found that cisplatin, platinol chemotherapy (CDDP) might induce VEGF through miR-144 levels suppression in PrC cells, with cell autophagy inhibition. Another study by Gu H et al found that miR-124 and miR-144 directly targeted the 3 UTR of PIM1 and, via its downregulation, led to hypoxia-induced autophagy and increased radiosensitivity of PrC [122]. Zheng H et al determined that miR-144-3 prevents proliferation and leads to cell death in PrC by targeting CEP55 [123].…”
Section: Mir-144 In Prostate Cancermentioning
confidence: 99%